Statistical analysis of the influence of microstructure on damage in fibrous ceramic matrix composites. Issue 3 (6th February 2017) - Tracy, Jared; Daly, Samantha
Abstract: The effect of microstructure on cracking was analyzed in a CMC using statistical methods. It was determined that the amounts of coating surrounding fibers and their dispersion within the matrix influenced where cracks evolved in transverse plies. Linear models predicted that maximum principal strains in transverse fiber coatings increased as (i) the fiber coating area increased and (ii) the length of matrix ligament between fibers decreased. Logistic models indicated that the likelihood of transverse fibers residing on a matrix crack increased as the (i) ratio of coating to filament decreased, (ii) distance between fibers decreased, or (iii) coating area increased.